Morphological Characteristics and Cross-sectional Heterogeneity of Rill Erosion on Loess Slope - LIU Qing; SHEN Donghui; HE Jijun; LIU Zhuangzhuang; SUN Liying; CAI Qiangguo (Shuitu Baochi Xuebao)
［Objective］ To explore the variation patterns and cross-sectional distribution characteristics of rill erosion and its morphological features. ［Methods］ Indoor artificially simulated rainfall experiments and 3D laser scanning were conducted to analyze the distribution of runoff, sediment yield and rill morphological characteristics of rill erosion under different rainfall and slope conditions. ［Results］ 1) When the rainfall intensity increased, the runoff and sediment yield increased significantly. When the rainfall intensity was 90 mm/h, the contribution rate of rill erosion to total erosion could reach more than 90%. 2) Rill width, depth, width-to-depth ratio and rill splitting degree were significantly affected by rainfall intensity, and all showed varying degrees of increase. Rill splitting degree and the maximum depth of rill showed a significant positive correlation with the amount of rill erosion. 3) Rill cross section varied greatly along the slope direction, the collapse of the gully wall was obvious. When the rainfall intensity was 60 mm/h, the rill cross section was mostly distributed in a "narrow and shallow" shape, When the rainfall intensity was 90 mm/h, the head and bottom of the rill were "narrow and shallow", the middle of the rill was "wide and deep" in general. The rill erosion in the middle was more severe. 4) When the rainfall intensity was 60 and 90 mm/h, the overall value range of rill cross-sectional index were 0.46—0.79 and 0.41—0.85, respectively. When the rainfall intensity was 60 mm/h, the volatility of rill cross-sectional index increased with the increase of slope gradient, indicating that spatial differentiation of rill cross section was more obvious, and variation of the rill cross section tended to be irregular. ［Conclusion］ The research results can provide some theoretical support for rill erosion prevention and control.